Tapis Cloth Transformation: Process and Product Innovation to Increase the Competitiveness of Lampung's Creative Industry - Hartono, Lili; Guntur, Guntur; Rustopo, Rustopo; Setiyono, Budi (Institut Seni Indonesia Denpasar, 2026)
Tapis cloth, with its unique and distinctive aesthetic value, has great potential to be developed into a culture-based creative industry. This study aims to analyze innovations in Lampung tapis cloth, especially in the manufacturing process and the resulting products, in order to encourage the development of the creative industry in Lampung. The main objective of this study is to identify and analyze innovations made in tapis cloth. This research is descriptive qualitative. Data collection used interview techniques, observation, and document analysis, with interactive data analysis methods. Innovations in the process and products of Lampung tapis cloth have a positive impact on the development of the tapis cloth industry in Lampung. With the use of more diverse materials and manufacturing techniques, such as wolfis cloth, velvet, and mixed decorative threads, as well as the application of ikat weaving and embroidery techniques, tapis cloth products become higher quality and more competitive. Innovations in tapis cloth products are carried out in aspects of the types and shapes of products made increasingly diverse. In addition, innovations in motifs that refer to old motifs with the addition of variations and modifications, as well as the creation of new motifs inspired by Lampung culture, make tapis cloth products increasingly unique and attractive. Innovations in the process and products of Lampung tapis cloth can encourage the development of the creative industry in Lampung Province.